Uncertainty in Projection of Climate Extremes: A Comparison of CMIP5 and CMIP6 - Zhang, Shaobo; Chen, Jie (Journal of Meteorological Research, 2021)
Climate projections by global climate models (GCMs) are subject to considerable and multi-source uncertainties. This study aims to compare the uncertainty in projection of precipitation and temperature extremes between Coupled Model Intercomparison Project (CMIP) phase 5 (CMIP5) and phase 6 (CMIP6), using 24 GCMs forced by 3 emission scenarios in each phase of CMIP. In this study, the total uncertainty ( T ) of climate projections is decomposed into the greenhouse gas emission scenario uncertainty ( S , mean inter-scenario variance of the signals over all the models), GCM uncertainty ( M , mean inter-model variance of signals over all emission scenarios), and internal climate variability uncertainty ( V , variance in noises over all models, emission scenarios, and projection lead times); namely, T = S + M + V . The results of analysis demonstrate that the magnitudes of S, M , and T present similarly increasing trends over the 21st century. The magnitudes of S, M, V , and T in CMIP6 are 0.94–0.96, 1.38–2.07, 1.04–1.69, and 1.20–1.93 times as high as those in CMIP5. Both CMIP5 and CMIP6 exhibit similar spatial variation patterns of uncertainties and similar ranks of contributions from different sources of uncertainties. The uncertainty for precipitation is lower in midlatitudes and parts of the equatorial region, but higher in low latitudes and the polar region. The uncertainty for temperature is higher over land areas than oceans, and higher in the Northern Hemisphere than the Southern Hemisphere. For precipitation, T is mainly determined by M and V in the early 21st century, by M and S at the end of the 21st century; and the turning point will appear in the 2070s. For temperature, T is dominated by M in the early 21st century, and by S at the end of the 21st century, with the turning point occuring in the 2060s. The relative contributions of S to T in CMIP6 (12.5%–14.3% for precipitation and 31.6%–36.2% for temperature) are lower than those in CMIP5 (15.1%–17.5% for precipitation and 38.6%–43.8% for temperature). By contrast, the relative contributions of M in CMIP6 (50.6%–59.8% for precipitation and 59.4%–60.3% for temperature) are higher than those in CMIP5 (47.5%–57.9% for precipitation and 51.7%–53.6% for temperature). The higher magnitude and relative contributions of M in CMIP6 indicate larger difference among projections of various GCMs. Therefore, more GCMs are needed to ensure the robustness of climate projections.